Nekaj možnosti bibliometrijske analize časopisa OZ 1998-2006 - Bizjak, Breda (Organizacija znanja, 2007)
The definition of bibliometrics as quantitative analysis of publications is followed by a brief outline of the history of the journal Organizacija znanja (Organisation of Knowledge; continuation of Cobiss obvetila). In addition to that, the following quantitative characteristics of this publication are analysed: authors, topics, citations. The conclusion focuses on the future development of Organizacija znanja.
Keywords: analize; bibliometrična analiza; bibliometrija; bibliotekarstvo; COBISS obvestila; informatika; information science; library science; Organizacija znanja; strokovne revije